Market Timing with Stock-Bond Correlation - Toivonen, Jaakko (My University, 2016)
The objective of the thesis is to study the market timing capabilities of the stock-bond correlation. Stock-bond correlation is a similar figure as BEYR, which is actively used in investing. Stocks and bonds are the most used financial instruments and their correlation measures their co-movement in a single figure. It would greatly benefit investors if this simple figure could be used as a guide in investing, in a similar way as BEYR is being used. The study included the SP500, low beta, high beta and corporate bond –indices and the timeframe is from 2006 to 2015. The methods used first test whether the stock-bond correlation works in timing the market and if the index beta affects this result. This is done with a strategy where extreme negative values of stock-bond correlation mark the switch from stocks to bonds. Secondly, an OLS regression is used to test if stock-bond correlation can predict stock returns and work as a market indicator. The results for the market timing capabilities are mixed. For corporate bonds, the active strategy using the stock-bond correlation beats the passive buy-and-hold strategy, which was the objective. For the other indices the passive strategies outperform the active ones, when observed during the entire investment period. The results for the regressions show that the correlation works in predicting corporate bond returns, but does not predict returns for any of the stock market indices.
Keywords: Stock-bond correlation; investment strategy; market timing; stock market indices; active strategies; fi=Laskentatoimi ja rahoitus|en=Accounting and Finance|; fi=Master's Degree Programme in Finance|